THE IMPORTANCE OF CIRCULAR ECONOMY FOR INTELLIGENT USE OF NATURAL RESOURCES - Bianchi, Naiara (Revista Interface Tecnológica, 2020)
In the past, it was kept in mind that it was not possible to measure the ways of intervention or modification of the environment, as well as their possible impacts, thus having no concern with environmental causes. But, today, there is a great environmental awareness expressed in legislation, popular conscience and pressure from international bodies. The main idea is to eliminate the concept of garbage, making all material remain within a cyclical flow, having its trajectory "from the cradle to the cradle", thus relaying its value. This intelligent reuse provides economic growth, as it no longer depends only on new resources, but on the reuse of existing ones, allowing raw materials to continue to increase their value. Thus, the circular economy has become an intentionally repairing or regenerative system, and this explanatory bibliographic research aims to demonstrate its operational and strategic benefits, as well as the gigantic potential for job creation, innovation and economic growth, proving to be a model capable of not only reducing the raw material, but also increasing innovations in industrial production processes.